Sleep, energy, and stress in collegiate female volleyball athletes - Foster, E.; Schumann, C.; Bunn, J. A. (Trends in Sport Sciences, 2023)
Introduction. Sleep duration and quality among collegiate athletes is of great importance for their recovery and has been linked to performance, but little is known about reasons for missed sleep or the relationship between sleep and stress in this population. Aim of Study. The aim of this study was to 1) assess the relationship between sleep quality, sleep duration, energy, and stress in female collegiate volleyball players through the four months of the competitive season, and 2) report the frequency of provided reasons for poor sleep quality and duration. Material and Methods. De-identified data from an athlete monitoring platform for sleep duration, sleep quality, stress, energy, and reasons for missed sleep were analyzed for this study. Data were gathered from a total of 67 female collegiate volleyball athletes during the competitive seasons from 2016 through 2021. Results. Sleep quality and sleep duration showed a moderate correlation (r = 0.404 to 0.552) across all four months of the volleyball season, p < 0.001. Sleep quality had a low correlation with energy for each month (r = 0.348 to 0.387), except September where there was a moderate correlation (r = 0.400, p < 0.001). Sleep quality and stress showed to no correlation (r = 0.184 to 0.266, p < 0.001). Sleep duration and energy showed low to no correlation (r = 0.160 to 0.246, p < 0.001). Sleep duration and stress were not correlated for any of the months evaluated (r = 0.091 to 0.195, p < 0.001). The results of the study also showed that "other", overtiredness, and worry/stress were the top reported sleep ailments for these athletes. Conclusions. These data can be applicable to coaches, athletes, and athletic trainers looking to gain insight on the sleep habits and effectiveness in collegiate female volleyball athletes during the competition season.